Flow rate impacts on capillary pressure and interface curvature of connected and disconnected fluid phases during multiphase flow in sandstone. (September 2017) - Herring, Anna L.; Middleton, Jill; Walsh, Rick; Kingston, Andrew; Sheppard, Adrian
Highlights: We conduct quasi-static flow experiments, under three flow rates, in sandstone. We link capillary pressure and image-based fluid–fluid interface curvatures. We investigate capillary pressure-saturation relationships for different flow rates. High capillary pressure (6.5 kPa) is successfully measured from image curvature. Large air snap-off events are observed during drainage for all flow conditions. Abstract: We investigate capillary pressure-saturation (PC -S) relationships for drainage-imbibition experiments conducted with air (nonwetting phase) and brine (wetting phase) in Bentheimer sandstone cores. Three different flow rate conditions, ranging over three orders of magnitude, are investigated. X-ray micro-computed tomographic imaging is used to characterize the distribution and amount of fluids and their interfacial characteristics. Capillary pressure is measured via (1) bulk-phase pressure transducer measurements, and (2) image-based curvature measurements, calculated using a novel 3D curvature algorithm. We distinguish between connected (percolating) and disconnected air clusters: curvatures measured on the connected phase interfaces are used to validate the curvature algorithm and provide an indication of the equilibrium condition of the data; curvature and volume distributions of disconnected clusters provide insight to the snap-off processes occurring during drainage and imbibition under different flow rate conditions.